Analysis of the Influence of Error on Load Sharing Characteristic of Planetary Transmission System - Zhou Lu; Wu Shijing; Li Jing; Wang Xiaosun; Zhu Weilin (Jixie chuandong)
A nonlinear transverse-torsional coupled dynamics model for planetary gear sets is established with considering time-varying meshing stiffness and gear backlash,and the changes of dynamic load sharing characteristics are analyzed when errors and error phase angles exist on individual or multiple components. The results show that the installation,eccentricity error of central components and eccentricity error of planetary gear make load sharing coefficient change periodically,while the installation error on planetary gear will make a sustained partial load for meshing pairs and the uneven load phenomenon is the most serious when error phase angle is in tangential direction. The error of planetary gear has the biggest effect on load sharing coefficient,and it is suggested to avoid error distribution on planetary gear. The load sharing performance is better when errors are distributed on adjacent planets than on non-adjacent planets or on one single planet. The effects on load sharing coefficient can be greatly Reduced when errors with the same amplitude and phase angle exist on all the planetary gears.